UNDERSTANDING THE RELATIONSHIP BETWEEN RESILIENCE AND WORK-LIFE BALANCE IN COLLEGE STUDENTS WORKING IN THE FASHION SECTOR - Aflaha, Nadia Nufida; Matulessy, Dr. Andik; Rini, Dr. Rr. Amanda Pasca (Srawung: Journal of Social Sciences and Humanities, 2024)
A good work-life balance in one's work can result in high morale, a sense of satisfaction in one’s work, and a sense of responsibility for one’s work and personal life. Individuals without work-life balance will experience an imbalance between work and personal life. Thus, achieving a work-life balance is essential. This research aims to determine the relationship between resilience and work-life balance in college students who work in the fashion sector. This research uses a correlational quantitative method with purposive sampling technique. The measurement tools used in this research used a resilience scale developed by Connor and Davidson. While the work-life balance measuring instrument uses a scale of aspects revealed by Greenhaus, Collin and Shaw. The subjects in this research are students who are studying and working in the fashion sector, which total 350 people, with the characteristics of students who are actively studying or not on leave, students who work in the fashion sector, not a full-time worker. Based on the results of this research, it is known that hypothesis is accepted with a pearson correlation value of 0.461 and p = 0.000 (p <0.05), which means that there is a positive and significant relationship between resilience and work-life balance in college students who work in the fashion sector. The results indicated that the higher the resilience, the higher the work-life balance of students who work in the fashion sector.